Money, Money, Money: Financial Literacy of Youth (Training and Practice : Journal of Educational Sciences, 2013)
Many studies have proven, that to recover from the economic crisis, the financial knowledge of the population needs to be broaden. This knowledge needs to be acquired already in school age, because today’s young are early forced to make economic decisions which will influence their future.The European Commission considers the financial education high-priority towards the formation of the single market, accordingly it encourages the EU citizens to acquire standard financial knowledge. In our country beginning with the 1st of September 2013. in the new Ntional curriculum the economical and financial education is part of the developmental fields, and from the 9 key competences it belongs to the initiative and entrepreneurial skill issue. In my study – based on international examples – I try to demonstrate, that those students who live in countries where the state pays more attention and subsidy to financial education, will more likely absolve with a higher education in finance. This has a significant utility for the individual and also for the society.